Optoelectronic memristive devices for retinomorphic application - 1 - Tun, Thaw Tint Te (Nanyang Technological University, 2023)
Today’s frame-based camera system generates a big amount of data, utilizes big storage space, consumes high power, and seems bulky. In comparison, the biological vision system including the retina preprocesses the sensed image data so that the amount of data transfer, power consumption, storage space, and the overall size are reduced. Thus, it is imperative to implement a retinomorphic camera system as a way of improving the current vision technologies. Optoelectronic memristive devices can be used to achieve that goal because of their property: coalescing sensing, memorizing, and computing in a single space. Many studies have been conducted toward this research direction, however, the complete and fully functioning retinomorphic system is not well realized yet. In this work, chalcogenide-based conductive bridge random access memory devices, with Ag/WTe2/Pt material stack in the form of a capacitor structure, were investigated for their potential to be used as high-density memory and most importantly in the retinomorphic system. After investigations, these optoelectronic memristive devices were found to be the best fit for high-density memory applications due to their bipolar, self- compliance, electroforming-free, highly repeatable, and multilevel memristive switching where the memory window was large (~103), and SET and RESET voltages were low with tight variability. The optical RESET property of the WTe2 devices was also confirmed, and they were believed to possess light-dosage tunable synaptic characteristics which are essential to perform pre-processing of the sensed image data like in biological vision systems. With the favorable optical properties confirmed in WTe2 devices, further works can be continued upon this work by fabricating a crossbar array structure that is also optimized for light sensing so that the potential usage of these devices for a retinomorphic system is fully unlocked, and engineering advances in vision technologies can progress.